Developing Edpuzzle-assisted e-Worksheet to Enhance Students' Critical Thinking Skills in Problem-based Learning - Firmansyah, Furqon; Andriyani, Andriyani (International Journal on Emerging Mathematics Education, 2023)
This study aims to produce an Edpuzzle-assisted mathematics e-worksheet that is feasible to improve the grade VII junior high school students’ critical thinking skills in problem-based learning. This study also aims to test the effectiveness of the e-worksheet in improving the critical thinking skills. It was a development research using 4D model (define, design, develop and disseminate). The results of this research show that the Edpuzzle-assisted mathematics e-worksheet is feasible to be used to improve the critical thinking skills of junior high school students in grade VII based on the validation of material experts, media experts, and students' responses. Furthermore, the e-worksheet is effective to improve the critical thinking skills of junior high school students in grade VII based on the results of gain score test with the category of increasing pre-test and post-test by 84.04%.